2022
DOI: 10.3390/gels8100650
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin/Tannin/ZnO Nanocomposite Hydrogel with Hemostatic Activities

Abstract: The inevitable bleeding and infections caused by disasters and accidents are the main causes of death owing to extrinsic trauma. Hemostatic agents are often used to quickly suppress bleeding and infection, and they can solve this problem in a short time. Silk fibroin (SF) has poor processibility in water, owing to incomplete solubility therein. In this study, aiming to overcome this disadvantage, a modified silk fibroin (SF-BGE), easily soluble in water, was prepared by introducing butyl glycidyl ether (BGE) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Hydrogels take up large volumes of liquid to attain hemostasis in large arterial bleeds. Several research groups have developed SF-based adhesives by tannic acid (TA) modification and photocuration. The abundant phenolic moieties present in TA offer a strong binding affinity toward the mucosal layer. Bai et al .…”
Section: Hemostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels take up large volumes of liquid to attain hemostasis in large arterial bleeds. Several research groups have developed SF-based adhesives by tannic acid (TA) modification and photocuration. The abundant phenolic moieties present in TA offer a strong binding affinity toward the mucosal layer. Bai et al .…”
Section: Hemostasismentioning
confidence: 99%
“…Although fibrin-based sealants are available for clinical applications, they are ineffective under dynamic conditions (e.g., beating heart, shear of blood flow) due to their poor adhesive strength on bleeding tissues. 118 Further, in an attempt to develop multifunctional hemostatic hydrogel, Yang et al 119 combined modified SF with ZnO nanoparticles. Herein, the authors chemically modified SF by introducing butyl glycidyl ether (BGE) into its side chain to obtain a water-soluble derivative (SF-BGE) ( Figure 7 Aa).…”
Section: Hemostasismentioning
confidence: 99%
“…Similar to copper nanoparticles, zinc nanoparticles have been found to promote blood clotting and prevent bleeding when applied to a wound. Several studies showed that zinc nanoparticles significantly accelerated blood clotting in vitro and demonstrated antibacterial activity [ 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of medicine is becoming more and more interdisciplinary, new methods of treatment are created. Interventional procedures are widely used [ 1 , 2 , 3 ], such as transarterial chemoembolization, catheter intra-arterial delivery of nanoparticles, etc. The possibilities of non-surgical and drug-free direct selective influence on individual cells in an external magnetic field by oscillations of magnetic nanoparticles fixed on the cell membranes or introduced into cells have been investigated [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%